Uulul Albaab dalam Perspektif Al-Qur’an - Salam, Eka Fitra Ramadani; Miswar, Andi; Halimah, Halimah (LP2M, Institut Agama Islam Qamarul Huda, 2025)
In the Quran there are 16 verses called Uulul Albaab; Muslim scholars understand, define, and describe